Tawuran antar remaja sebagai wujud rendahnya pemahaman terhadap nilai pancasila - 29, diah kumala (Maliki Interdisciplinary Journal, 2025)
Fights or feuds between groups of teenagers with each other so that it becomes a special concern for the general public and becomes a bad bugbear for society. This phenomenon is called brawls. The phenomenon of teenage brawls can change the personality and behavior of the teenagers. The purpose of this writing is to describe (1) to find out the factors that cause brawls between teenagers (2) to find out the prevention of teenage brawls. Methodologically, this study is included in the category of literature review. Data is analyzed with the aim of formulating policies and impacts related to brawls between teenagers as a case that is quite concerning in society. The results of this study include (1) factors that cause brawls between teenagers, namely low religious values, understanding of Pancasila norms and values, and low awareness to obey the law (2) prevention so that teenage brawls do not get worse, the need for supervision from parents and protecting children from peer relationships and paying attention to the environment in children's relationships.